Sensitivity of polar stratospheric cloud formation to changes in water vapour and temperature - Khosrawi, F.; Urban, J.; Lossow, S.; Stiller, G.; Weigel, K.; Braesicke, P.; Pitts, M. C.; Rozanov, A.; Burrows, J. P.; Murtagh, D. (European Geosciences Union, 2015)
More than a decade ago it was suggested that a cooling of stratospheric temperatures by 1 K or an increase of 1 ppmv of stratospheric water vapour could promote denitrification, the permanent removal of nitrogen species from the stratosphere by solid polar stratospheric cloud (PSC) particles. In fact, during the two Arctic winters 2009/10 and 2010/11 the strongest denitrification in the recent decade was observed. Sensitivity studies along air parcel trajectories are performed to test how a future stratospheric water vapour (H2O) increase of 1 ppmv or a temperature decrease of 1 K would affect PSC formation. We perform our study based on measurements made during the Arctic winter 2010/11. Air parcel trajectories were calculated 6 days backward in time based on PSCs detected by CALIPSO (Cloud Aerosol Lidar and Infrared Pathfinder satellite observations). The sensitivity study was performed on single trajectories as well as on a trajectory ensemble. The sensitivity study shows a clear prolongation of the potential for PSC formation and PSC existence when the temperature in the stratosphere is decreased by 1 K and water vapour is increased by 1 ppmv. Based on 15 years of satellite measurements (2000–2014) from UARS/HALOE, Envisat/MIPAS, Odin/SMR, Aura/MLS, Envisat/SCIAMACHY and SCISAT/ACE-FTS it is further investigated if there is a decrease in temperature and/or increase of water vapour (H2O) observed in the polar regions similar to that observed at midlatitudes and in the tropics. Although in the polar regions no significant trend is found in the lower stratosphere, we found from the observations a correlation between cold winters and enhanced water vapour mixing ratios.